An Expert Elicitation on the Effects of a Ban on Menthol Cigarettes and Cigars in the United States. Issue 11 (7th June 2021) - Levy, David T; Cadham, Christopher J; Sanchez-Romero, Luz Maria; Knoll, Marie; Travis, Nargiz; Yuan, Zhe; Li, Yameng; Mistry, Ritesh; Douglas, Clifford E; Tam, Jamie; Sertkaya, Aylin; Warner, Kenneth E; et al.
Abstract: Introduction: The US Food and Drug Administration announced its intention to ban menthol in cigarettes. However, information is needed on how a federal ban would affect population health. Aims and Methods: We conducted an expert elicitation to gauge the impact of a menthol cigarette and cigar ban in the United States. We developed and pilot tested a questionnaire that focused on tobacco use transitions of current smokers (age 18–24 menthol, age 35–54 menthol, and age 35–54 nonmenthol) and potential menthol smokers (age 12–24). Using a structured expert elicitation, we estimated mean net transitions under a ban from cigarette use to combustible tobacco product, smokeless tobacco, novel nicotine delivery product (NNDPs, such as e-cigarettes) use, or no tobacco use. Results: Eleven experts provided responses. Of those ages 12–24 who would have initiated menthol cigarette use in the absence of a ban, the experts estimated that 41% would still initiate combustible products under a ban, while 18% would initiate with NNDPs and 39% would not initiate regular tobacco use. Combustible use by menthol smokers ages 35–54 was expected to decline by 20% postban relative to preban rates, half switching to NNDPs and half quitting all tobacco use. Menthol smokers ages 18–24 were expected to reduce combustible use by 30%, with 16% switching to NNDPs. Greater reductions in combustible use were estimated for African Americans across the three age groups. Negligible impacts were expected for current adult nonmenthol smokers. Conclusions: According to expert opinion, a menthol ban is expected to substantially reduce smoking initiation and combustible tobacco product use among current menthol smokers. Implications: The US Food and Drug Administration recently announced its intention to ban menthol in cigarettes, but information on the potential impact on smoking and other nicotine product use is limited. We conducted an expert elicitation to gauge the impact of a menthol cigarette and cigar ban in the United States. A panel of experts estimated that menthol smokers ages 35–54 would reduce combustible tobacco use by 20%, with half switching to e-cigarettes and half quitting all nicotine use. Larger reductions were expected at younger ages, and menthol smoking initiation was reduced by 59% with 18% instead using e-cigarettes. African Americans were expected to have greater reductions in combustible tobacco use than the rest of the population.